Pengaruh Kualitas Produk Dan Citra Merek Terhadap Niat Beli Ulang Dengan Kepuasan Pelanggan Sebagai Variabel Mediasi Pada Kasur Busa Merek Royal Foam Di Denpasar - Jaya Utomo, Andre; Rahyuda, I Ketut (Relasi : Jurnal Ekonomi, 2024)
The aim of this study to examine and explain the effect of product quality, brand image, and customer satisfaction in growing repurchase intentions on Royal Foam brand foam mattresses.This research is classified as an associative quantitative research conducted in the city of Denpasar. The data consists of 102 samples, collected by distributing questionnaires using the Google Form. The criteria for respondents in this study were customers who had purchased and used a foam mattress with the Royal Foam brand, domiciled in Denpasar City. The analysis technique used is the Structural Equation Model (SEM) and uses the SmartPLS 4.0 analysis tool. The results showed that product quality had a positive and insignificant effect on repurchase intention, brand image had a positive and significant effect on repurchase intention, product quality had a positive and significant effect on customer satisfaction, brand image had a positive and significant effect on customer satisfaction, customer satisfaction on repurchase intention had a positive and insignificant effect on Royal Foam brand foam mattresses in Denpasar City. The next result is satisfaction being able to mediate the effect of product quality on repurchase intentions. Satisfaction is not able to mediate the influence of brand image on repurchase intention on foam mattresses with the Royal Foam brand in Denpasar City